Estresse percebido de uma amostra de idosos do Distrito Federal: relações com a pandemia e infodemia de Covid-19 - Jesus, Aline Araujo (2022)
COVID-19 pandemic has been marked by a phenomenon called infodemics. This term is related to the propagation of too much information, including false or misleading, within a short period of time, making it difficult to identify reliable sources, thus, impairing the interpretation and the judgment of the receiver. Studies have shown the existence of relationship between infodemics and psychological suffering, such as anxiety, sadness, fear, and stress, in the general population. Since elderly people is one of the main risk groups for COVID-19, it is necessary to understand the relationship between infodemics and mental health variables for people at this stage of life. Thus, this research aimed to analyze the relationship between perceived stress and COVID-19 infodemic in elderly people living in the Federal District of Brazil. Therefore, this quantitative, descriptive, and cross-sectional study was conducted. Primary data were collected through an electronic form composed of a demographic questionnaire, with items for sample characterization and related to the infodemic, and by the Perceived Stress Scale (PSS). A total of 154 elderly people participated in the study, aged between 60 and 90 years, most of them female (66.20%), white (55.19%), married (48.05%), living in urban areas (93.51%) and with higher education (49.35%). As for exposure to news about COVID-19, television (46.75%) and social networks (38.31%) were the most frequently accessed media, especially television (77.92%) and WhatsApp (61.92%). Regarding news and information about COVID-10, media that most affected individuals was television, followed by social networks. Likewise, elderly people who reported being affected by the information broadcast, whether on television or social networks, had higher values of perceived stress, compared to those who did not use these media or who did not consider themselves to have been affected by the information disclosed therein. Elderly people affected by information broadcast on television about the number of deaths had higher PSS values than those who do not use this medium. Participants who used WhatsApp and Telegram to access the news also showed higher values of perceived stress. The results showed, in general, a behavior profile in which the variables related to the means of communication, frequency and duration of exposure to news about COVID-19, and issues related to income, are related to stress. It is expected, therefore, that this study stimulates the development of others, whose objectives are, for example, to investigate the consequences of the infodemic on the mental health of the elderly, as well as contribute to the reformulation of public policies aimed at inclusion and digital education.